BODY IMAGE IN DIABETES MELITUS PATIENTS WITH ULCUS DIABETIC IN GRESIK - Muhalla, Hafna Ilmy (Journal of Vocational Nursing, 2020)
Introduction: Indonesia is ranked 4th in the world for the number of diabetics according to WHO, and most of diabetics experience complications, one of which is ulcer diabetikum. This can be a trigger for the emergence of body image disorders from diabetics, so researchers need to know the picture of ulcus sufferers' body image to later be mapped and make it easier in subsequent handling. The research objective is to describe the image of body image in patients with diabetes mellitus with ulcus complications. Physical changes in the body can affect body image and self-esteem Methods: Design of this study used a descriptive research design, the population in this study were all patients who have diabetes mellitus with ulcus diabeticum in Ibnu Sina Hospital Gresik regency with a sample of 20 respondents, samples were taken by using purposive sampling technique. Data collection using questionnaires with 15 multiple choices question. Furthermore, the data were analyzed with coding, scoring, tabulating presentatif, and described. Results: The results showed a total of 20 respondents obtained ii'om 5 respondents (25%) have a good body image, 7 respondents (35%) had a poor body image and 8 respondents (40%) who did not have a good body image.  Conclusion: Based on the results of this study indicate that in patients with diabetes mellitus who are already experiencing complications of ulcus diabetic almost half of respondents do not have a good body image, and a small proportion of respondents have a good body image. This is due to several factors, namely the respondents admitted that the wounds on his legs is a sign of personal failure on him therefore to improve body image and the changing assessment of the physical condition and provide social support.